PENINGKATAN KETERAMPILAN KOMUNIKASI INTERAKTIF: PENGUATAN PELAYANAN DAN INTERAKSI WISATA DI DESTINASI BOJONG KULUR - Angela Kayleen Hardiyanto; Johannes Kurniawan (LPPM Institut Pendidikan Nusantara Global, 2026)
Bojong Kulur Tourism Village has natural tourism potential through river cruising activities and the development of MSMEs, but still faces challenges in visitor interaction due to the limited communication skills of the tour guides. Based on these conditions, this Community Service Program (PkM) was implemented to improve interactive communication skills and storytelling abilities, enabling guides to create more engaging and informative tourism experiences. The main objective of this program was to provide an understanding of interactive communication principles and narrative structuring techniques relevant to river tour guiding. The implementation methods included material presentations, narrative development practice, storytelling delivery, and evaluation through pre-test, post-test, and feedback forms. The program was conducted on 20 November 2025 and was attended by 26 participants. The evaluation results indicated an increase in participants’ knowledge, as reflected in the difference between pre-test and post-test scores, as well as positive responses regarding the clarity and relevance of the material. Overall, this PkM activity successfully strengthened participants’ foundational interactive communication competencies, supported the improvement of tourism service quality, and contributed to enhancing community capacity in destination management. These findings highlight the need for continued training to maintain consistency and quality of services in Bojong Kulur Tourism Village.